2022
DOI: 10.3390/ijgi11020113
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Sensitivity Analysis in Seismic Risk with Probabilistic Building Exposure Models: An Application in Valparaíso, Chile Using Ancillary Open-Source Data and Parametric Ground Motions

Abstract: Efforts have been made in the past to enhance building exposure models on a regional scale with increasing spatial resolutions by integrating different data sources. This work follows a similar path and focuses on the downscaling of the existing SARA exposure model that was proposed for the residential building stock of the communes of Valparaíso and Viña del Mar (Chile). Although this model allowed great progress in harmonising building classes and characterising their differential physical vulnerabilities, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 99 publications
0
1
0
Order By: Relevance
“…The functional form of both GMPEs is similar, and therefore, their predictions do not differ significantly, as observed in previous studies (e.g., Hussain et al, 2020;Gómez-Zapata et al, 2022a). In particular, Hussain et al ( 2020) found negligible differences in direct loss estimates for the residential building stock of Santiago de Chile after using these two GMPEs to simulate the associated ground motion from subduction earthquake scenarios.…”
Section: Ground Motion Modelssupporting
confidence: 70%
See 2 more Smart Citations
“…The functional form of both GMPEs is similar, and therefore, their predictions do not differ significantly, as observed in previous studies (e.g., Hussain et al, 2020;Gómez-Zapata et al, 2022a). In particular, Hussain et al ( 2020) found negligible differences in direct loss estimates for the residential building stock of Santiago de Chile after using these two GMPEs to simulate the associated ground motion from subduction earthquake scenarios.…”
Section: Ground Motion Modelssupporting
confidence: 70%
“…We employ the Bayesian exposure model of the building stock with the building classes described in (Gómez-Zapata et al, 2022a) and available in (Pittore et al, 2021a). The model was constructed by taking the OpenStreetMap footprint of the buildings in the two communes, and assigning to each footprint the most likely building class.…”
Section: Model For the Building Stock In The Communes Of Valparaíso A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Volunteered geographic information and building-by-building exposure models, sensitivity analysis of seismic risk with probabilistic building exposure models [25,26] Seismic risk scenarios for residential buildings…”
Section: Methodological Approach Citationmentioning
confidence: 99%
“…Recently, novel approaches relying on satellite images and/or open-accessible geospatial data have been developed to set up seismic exposure models (Geiß et al, 2017;Gomez-Zapata et al, 2022;Krayem et al, 2021;Nievas et al, 2022;Sousa et al, 2017;Wieland et al, 2012). Particularly, in countries with limited census data and incomplete building datasets, such as Lebanon, volunteered geographic information, such as the data provided by OpenStreetMap (OSM) (https://www.openstreetmap.org/) are valuable resources for the development of up-todate building exposure models (e.g.…”
mentioning
confidence: 99%